The Effectiveness of Gamification in Improving Motivation and Learning Outcomes in Primary School Mathematics: A Systematic Literature Review - Yuliana Novita Sari; Elizar; Berta Apriza (Universitas Pendidikan Ganesha, 2026)
Mathematics learning in elementary schools still faces challenges, particularly low motivation and learning outcomes due to abstract material and a lack of varied methods. Gamification, the application of game elements in learning, is an innovative approach to increasing student engagement. This study aims to systematically examine the effectiveness of gamification in improving the motivation and learning outcomes of elementary school students in mathematics. The method used was a Systematic Literature Review (SLR) with articles sourced from Google Scholar for the period 2021–2025. Selection was carried out using specific inclusion criteria until ten articles were obtained for in-depth analysis. The analysis was conducted by reviewing the characteristics of the research, the forms of gamification implementation, and its impact on motivation and learning achievement. The study results show that gamification consistently has a positive impact on motivation, activeness, and mathematics learning outcomes. The use of elements such as points, levels, challenges, and feedback can create a more engaging, enjoyable, and meaningful learning experience. The effectiveness of gamification is even stronger when combined with contextual approaches, such as Problem-Based Learning and Realistic Mathematics Education, because it helps students master mathematical concepts in real-life situations. However, the success of gamification implementation depends heavily on the quality of the learning design, its suitability to the classroom context, and the teacher’s readiness and competence in managing it. With proper planning, gamification has the potential to be an effective alternative strategy for sustainably improving the quality of mathematics in elementary schools.